Analysis and Implementation of LQR and LQT Control Strategies for the Maxon RE36 DC Motor Using MATLAB Simulink Environment - Nugraha, Anggara Trisna; Mukhammad Jamaludin; Rama Arya Sobhita; Dimas Eka Saputra (SAINSTECH NUSANTARA, 2025)
The field of automatic control plays a crucial role in advancing science and technology. Among various actuators, DC motors are widely used but are often prone to overshoot due to their high initial torque and generally unstable performance characteristics. This study aims to determine the most effective control approach for optimizing the performance of the Maxon RE36 DC motor. Two control strategies are evaluated: the Linear Quadratic Regulator (LQR) and the Linear Quadratic Tracking (LQT) method. In a first-order system analysis, the motor's output significantly deviated from the target setpoint of 1, exhibiting an overshoot of approximately 0.505%. The application of the LQR method in output response modeling effectively reached the setpoint without any occurrence of overshoot or undershoot. Conversely, the LQT method achieved the setpoint but introduced a 5.851% undershoot and a 0.7% overshoot, although it demonstrated a rapid response time, achieving steady-state within approximately ±0.5 seconds.Experimental results on the Maxon RE36 DC motor revealed that while the LQT method offered faster settling times, the LQR method produced a cleaner response with no overshoot or ripple, making it more suitable for precision optimization of the motor's dynamic performance.